Analysis of Respondents’ Characteristics with Tuberculosis and Adherence Using Morisky Medication Adherence Scale - Ratnasari, Nita Yunianti; Hastuti, Weni; Soares, Domingos; Carvalho, Joaquim Gregorio de; Ximenes, Jose Dionisio; Gaio, Eduardo C (Jurnal Kesehatan Masyarakat, 2024)
Tuberculosis (TB), an infectious disease caused by Mycobacterium tuberculosis, results in approximately 10 million new cases and 1.5 million deaths annually worldwide. This research method is an observational analytical study using a cross sectional design. The target population of this study were all patients with Pulmonary TB who completed the intensive stage of treatment and participated in the DOTS program at selected health centers during the three months, namely patients diagnosed with Tuberculosis and registered as outpatients at the Hospital Nacional Guido Valadares ( HNGV) Dili, Klibur Domin Tibar, Liquiça and at the Hospital Sentru Saúde Bairro Pite, Dili, Timor-Leste. The inclusion criteria in this study involved tuberculosis patients who were receiving anti-tuberculosis drug therapy for at least four weeks since the initial stage of treatment, aged more or equal to 17 years and able to understand oral and written instructions. Data collection took place between September and November 2023, involving a sample of 69 respondents. These results provide an overview of respondent characteristics that are significant in analyzing treatment adherence in patients with pulmonary TB. Tuberculosis is a contagious disease caused by infection with the Mycobacterium tuberculosis germ, usually affecting not only the lungs but also other organs.